Force-length relationships of human gastrocnemius and soleus muscles in vivo - Sakuma, J.; Mitsukawa, N.; Kawakami, Y.; Fukunaga, T. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
Synergistic muscle have different architecture, and therefore could have different force-length relationships for the same joint angle changes. Previous studies have failed to reveal the force-length relationships of synergistic muscles. The purpose of this study was to investigate the force-length relationships of the triceps surae muscles for humans in vivo.